Changes produced by external radiation in parameters influencing intestinal permeability and microparticle uptake in vitro. - Moyes, S; Killick, E; Morris, J; Kadhim, M; Hill, M; Carr, K (2008)
PURPOSE: To determine the interaction between X-irradiation and in vitro intestinal microparticle uptake through Caco-2 epithelial cells. METHODS: Caco-2 cells were cultured on 3 microm porous membranes for 21 days, X-irradiated with 2 Gy or sham-irradiated, then incubated for 5 or 30 min and exposed apically for 30 min to 2 microm latex microparticles. Measurements included cell dimensions, from confocal microscope 'optical slices'; transepithelial resistance (TER) for tight junction (TJ) permeability; particle aggregation; and particle numbers on (adsorbed), in (intraepithelial) and through (submembranous) the epithelium. RESULTS: Irradiation alone reduced TJ permeability more than sham-treatment, more so 5 min than 30 min after treatment. Irradiated epithelia were more permeable to particles than the equivalent sham-irradiated or previously untreated (particle only) groups: the latter two were similar. Irradiation altered adsorbed particle numbers and increased submembranous counts: particle uptake correlated best with cell height. CONCLUSIONS: 2 Gy X-irradiation increased particle uptake and translocation through the epithelium. This correlated well with the TJ opening seen after particle exposure in irradiated samples and changes in cell morphology. New data on cell dimensions underlined the similarity in particle uptake between this in vitro epithelium and that in an in vivo model, highlighting the translational significance of the work.